2001
DOI: 10.1007/s004390000424
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Y chromosome DNA haplotypes and Y chromosome deletions leading to male infertility

Abstract: Microdeletions on the short arm of the Y chromosome have defined three non-overlapping regions (AZFa, b, c) recurrently deleted among infertile males. These regions contain several genes or gene families involved in male germ-cell development and maintenance. Even though a meiotic origin for these microdeletions is assumed, the mechanisms and causes leading to microdeletion formation are largely unknown. In order to assess whether some Y chromosome groups (or haplogroups) are predisposed to, or protected again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
0
14
1
1
Order By: Relevance
“…In Asian populations, although the correct distribution pattern of Y haplogroups is still not known, haplogroup N, which is susceptible to spontaneous gr/gr deletions, is reported to be common in this region (Fernandes et al, 2004). Other reports failed to find an association between Y haplogroups and gr/gr deletions when studying less homogenous populations (Paracchini et al, 2000;Quintana-Murci et al, 2001;Carvalho et al, 2003). In our study, 54.16% of infertile men who carried the gr/gr deletion belonged to haplogroup E3b2.…”
Section: Discussioncontrasting
confidence: 60%
“…In Asian populations, although the correct distribution pattern of Y haplogroups is still not known, haplogroup N, which is susceptible to spontaneous gr/gr deletions, is reported to be common in this region (Fernandes et al, 2004). Other reports failed to find an association between Y haplogroups and gr/gr deletions when studying less homogenous populations (Paracchini et al, 2000;Quintana-Murci et al, 2001;Carvalho et al, 2003). In our study, 54.16% of infertile men who carried the gr/gr deletion belonged to haplogroup E3b2.…”
Section: Discussioncontrasting
confidence: 60%
“…Similarly to AZFa region, there could be differing susceptibilities to the other AZF deletions depending on the Y chromosome structure. Men carrying Y chromosome microdeletions from Ireland, Scotland, Germany, Italy, Spain, Holland and Denmark were haplotyped and the haplotype distribution was then compared to infertile men without microdeletions (59) or compared to an unselected male control population (60). Y chromosome microdeletions were found to occur on different Y chromosome backgrounds and there was no significant difference between Y chromosome haplogroup distribution in the study and control groups.…”
Section: Azf Deletions and Y Chromosome Backgroundmentioning
confidence: 99%
“…In particular, only three studies have investigated the possible association between Y-chromosome haplogroups and AZF deletions, [10][11][12] all of them failing to establish important associations. These works studied such associations in an European population involving 73 microdeleted samples of heterogeneous geographical origin, 10 in a northwestern European population involving 50 patients 11 and in a Japanese population, more geographically localised but represented by a very low number of people with microdeletions (six patients). 12 All the previous studies that found some suggestion of an association with Y-chromosome haplogroups dealt with infertility.…”
mentioning
confidence: 99%